2018
DOI: 10.1002/oca.2477
|View full text |Cite
|
Sign up to set email alerts
|

LQ control of unknown discrete‐time linear systems—A novel approach and a comparison study

Abstract: In this paper, we propose a novel approach to the linear quadratic (LQ) optimal control of unknown discrete-time linear systems. We first describe an iterative procedure for minimizing a partially unknown static function. The procedure is based on simultaneous updates in the estimation of unknown parameters and in the optimization of controllable inputs. We then use the procedure for control optimization in unknown discrete-time dynamic systems-we consider applications to the finite-horizon and the infinite-ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…. Now, it can be shown that there exists a finite horizon admissible control of length 2 so that corresponding cumulative cost V (2) (e k ) is related to V (1) (e k ). To that end, we construct finite horizon admissible control of length 2:…”
Section: Convergence Analysis Of Iterative Adp Algorithmmentioning
confidence: 99%
See 1 more Smart Citation
“…. Now, it can be shown that there exists a finite horizon admissible control of length 2 so that corresponding cumulative cost V (2) (e k ) is related to V (1) (e k ). To that end, we construct finite horizon admissible control of length 2:…”
Section: Convergence Analysis Of Iterative Adp Algorithmmentioning
confidence: 99%
“…Optimal control for nonlinear systems requires solving the nonlinear Hamilton-Jacobi-Bellman (HJB) equation analytically which is usually too difficult. 1,2 To that end, the usefulness of dynamic programming (DP) for solving HJB equation is well established. [3][4][5] Adaptive dynamic programming (ADP) based methods have emerged as effective approach for solving nonlinear HJB in approximative sense and solve the optimal control problems forward-in-time.…”
Section: Introductionmentioning
confidence: 99%
“…We treat each row r k of A separately. Denoting by y j the right hand side in (7), we can write its k-th component as…”
Section: Nmentioning
confidence: 99%
“…Finally, let us mention that other works have already dealt with LQR problems with unknown dynamics (see i.e. [4,5,7,9] and references therein), but they all need several trials to converge, whereas our method works with just one.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, let us mention that other works already dealt with LQR problems with unknown dynamics (see i.e. [4,5,7,9] and references therein), but they all need several trials to converge, whereas our method works with just one simulation.…”
Section: Introductionmentioning
confidence: 99%